A case study of strategic human resource management: implementation levels and communication. (4th May 2021) - McCann, Ryan; Allen, Stuart
The communication of information relevant to strategic human resource management (SHRM) has the potential to support SHRM implementation and should be reflected in the activity of an organisation's inter- and intra-organisational communication networks as forms of organisational information processing. This multiple case study examined SHRM implementation levels in a sample of oil and gas companies with the aim of examining the extent to which communication flows reflect the level of SHRM implementation. The case studies showed similarly low levels of SHRM-related communication and SHRM implementation, suggesting the need for further research to explore this relationship. The authors propose that SHRM-related communication could be an additional factor in assessing SHRM implementation levels and that organisational design must be considered in understanding low levels of SHRM-related communication.